2012
DOI: 10.1111/rda.12044
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of Domestic Cat Oocytes – Effect on Viability and Integrity of Subcellular Structures

Abstract: ContentsCryopreservation of female gametes is a crucial part of assisted reproduction techniques. The domestic cat is a model for both wild felids and human research. The aim of this study was to evaluate the effect of different vitrification protocols applied to feline oocytes at different maturational stages on the preservation of oocyte viability and integrity of subcellular structures. The vitrification solutions consisted of 20% ethylene glycol, 20% DMSO, 20% FCS, and 1.5 M Trehalose with and without 10% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 12 publications
1
24
0
4
Order By: Relevance
“…In addition to protecting nuclear membrane integrity, desiccation approach also performed better at maintaining GV chromatin conformation than vitrification. Condensed chromatin observed in the cryopreserved samples has been described in previous reports (Falk et al, ; Mikołajewska et al, ; Royere, Hamamah, Nicolle, & Lansac, ). Although ice crystal formation is the usual culprit for cryoinjuries, several other factors during cryopreservation procedure could also impact DNA structure (Kopeika et al, ).…”
Section: Discussionsupporting
confidence: 78%
“…In addition to protecting nuclear membrane integrity, desiccation approach also performed better at maintaining GV chromatin conformation than vitrification. Condensed chromatin observed in the cryopreserved samples has been described in previous reports (Falk et al, ; Mikołajewska et al, ; Royere, Hamamah, Nicolle, & Lansac, ). Although ice crystal formation is the usual culprit for cryoinjuries, several other factors during cryopreservation procedure could also impact DNA structure (Kopeika et al, ).…”
Section: Discussionsupporting
confidence: 78%
“…The debate on how vitrification procedures affect the microfilament network of the immature or mature oocytes has been reported in several studies [8,13,[17][18][19][20][21][38][39][40]. Consequences of vitrification/warming on the actin cytoskeleton depended on the CPAs used, the oocyte maturation stage and varied between species.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the exposure to cryoprotectants and the cold temperatures may lead to the disruption of microtubules and the change of the meiotic spindle morphology of mature oocytes [11][12][13][14][15][16]. Few reports focus on modifications caused by vitrification on the actin cytoskeleton [13,[17][18][19][20][21]. Actin is a major component of the cytoskeleton of the oocyte and it is present as the fibrous polymer, F-actin, in dynamic equilibrium with monomeric globular actin (G-actin).…”
Section: Introductionmentioning
confidence: 99%
“…La criopreservación de ovocitos se ha logrado con diversos grados de éxito en las pocas especies en que ha sido ampliamente estudiado, incluyendo el gato doméstico. Aunque han nacido gatitos después de una tasa de criopreservación controlada y transferencia de embriones derivados in vitro e in vivo, la criopreservación de ovocitos de gato sigue siendo un área urgente de mayor exploración (Cocchia et al, 2010;Pope et al, 2012) ya que todavía no se considera una herramienta confiable y repetible (Apparicio et al, 2013;Mikolajewska et al, 2012).…”
Section: Introductionunclassified